PENGEMBANGAN MULTIMEDIA INTERAKTIF DENGAN PERMAINAN ULAR TANGGA BERBANTUAN WEBSITE GENIALLY PADA MATERI OPERASI HITUNG PERKALIAN SISWA KELAS III SD NEGERI 4 BAJULAN - Riska Melati; Kharisma Eka Putri; Alfi Laila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the results of a needs assessment questionnaire from a third-grade teacher at SD Negeri 4 Bajulan, which showed problems in learning mathematics on multiplication and the lack of use of interactive learning media. The purpose of this study was to determine the validity, practicality, and effectiveness of interactive multimedia with the snakes and ladders game assisted by the Genially website on the multiplication arithmetic operation material for third-grade students at SD Negeri 4 Bajulan. This development research produced an interactive multimedia product with the snakes and ladders game assisted by the Genially website. The method used for this research is R&D with the ADDIE model which consists of 5 stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Data collection techniques use questionnaires, interviews, and tests. The data analysis technique used is a Likert scale. The source of validity data is obtained from media expert questionnaires and material expert questionnaires. The source of effectiveness data is obtained from the results of the evaluation which is compared with the KKM and then sought for classical completeness. And the practicality of the media is obtained from the teacher and student practicality questionnaire. The results of the research on the Development of Interactive Multimedia with the Snakes and Ladders Game Assisted by the Genially Website are as follows: (1) Interactive Multimedia with the Snakes and Ladders Game Assisted by the Genially Website obtained a percentage score of material validation results of 100% and the results of media validation obtained a percentage score of 86% meaning it is included in the